Georgia : An Integrated Trade Development Strategy - World Bank (Washington, DC, 2013)
Georgia became a member of WTO in June 2000. It has low import tariffs and no quantitative restrictions. The VAT (20 percent) and excise taxes are equally applied to imports and domestic output. However, the implementation of trade policies is undermined by corruption and poor customs and tax administration. Moreover, a new tariff schedule adopted in January 2003 increased the number of tariffs from four to 22! and the top duty rate from 12 to 30 percent. Although the weighted average tariff will go up only by a fraction of a percent and the new tariffs are in line with the upper bounds agreed with the WTO upon accession, such a schedule is a step back from the previous, simpler schedule. Georgia faces no significant trade barriers in world markets and main export destinations include the Commonwealth of Independent States (CIS) region (45 percent)-e.g., Russia, Azerbaijan, Ukraine, and Armenia- where Georgia enjoys duty-free access, followed by Turkey (20 percent), and the EU (18 percent)-mainly Germany. Like most CIS countries, the cost of doing business in Georgia is high and adds significant investment risk. Not surprisingly, outside of two large energy project, foreign direct investment (FDI) in Georgia has been insignificant. According to the 2002 Business Environment and Enterprise Performance Survey (BEEPS) conducted in Georgia, taxation and corruption are the main obstacles to doing business. Along with crime, these problems are somewhat worse in Georgia than its regional counterparts. Issues relating to regulations, the judiciary, infrastructure, and access to finance while still problematic appear more or less the same across the CIS region. More specifically, the industry case studies conducted for this study identified several institutional constraints which significantly undermine the export competitiveness of Georgian firms and create barriers to entry, a critical issue for a transition economy. Notably, exporters do not have assured access to inputs at world prices, particularly of those procured in the domestic market, because of the lack of a functioning VAT refund mechanism.